Loading of deuterium and helium by Pilot-PSI plasma and their detection by in-situ LIBS. (August 2017) - Piip, K.; van der Meiden, H.J.; Bystrov, K.; Hämarik, L.; Karhunen, J.; Aints, M.; Laan, M.; Paris, P.; Seemen, H.; Hakola, A.; Brezinsek, S.
Highlights: In this study we tested in-situ LIBS for deuterium and helium detection tungsten coatings. We managed to detect deuterium with 1.2 mbar argon background pressure. Helium was successfully detected without addition background gas. LIBS was found to be a suitable in-situ tool for deuterium and helium detection from tungsten coatings. Abstract: Laser-induced breakdown spectroscopy (LIBS) is a promising method for quantifying the fuel content of the plasma-facing components of ITER both in between plasma discharges ( in-situ ) and after maintenance operations. The aim of the present study is to test the applicability of in-situ LIBS for monitoring deuterium (D) and helium (He) content of W samples exposed to fusion relevant plasma fluxes in the linear plasma device Pilot-PSI. The D loading was performed during 1000 s of plasma exposure at low (200-300 ° C) surface temperatures. Despite of low intensity and noisy LIBS spectra, H and D lines, at 656.1 and 656.3 nm, respectively, could be fitted with Lorentzian contours and reliably resolved at 1.2 mbar background pressure of argon. In the case of He loading, the samples were also exposed to plasma during 1000 s while the surface temperature reached values up to 720 ° C at the center. Already at 10 – 2 mbar residual pressure of the device, the He I line at 587.6 nm was visible for the first 2–3 laser shots. We demonstrated that in-situ LIBS is a reliable method for detection of He and D retention in ITER-relevant materials. Nevertheless, for measuring relative and absolute concentrations of D and He in the ITER-relevant samples, further studies are needed.